Applications of a Preferential–Solvation Index (Psi) for the Comparison of Binary Mixtures with Ionic Liquids - Caroli-Rezende, M; Morales-Lovera, S; Pastenes, C (Elsevier B.V., 2021)
Applications of a preferential–solvation index (PSI) for comparing analogous binary mixtures with ionic liquids (ILs) are described with the analysis of more than sixty examples from the literature. Interesting trends and patterns are revealed, confirming conclusions based on more elaborate treatments, or disclosing puzzling discontinuities by comparison of analogous mixtures. The obtained trends also question the meaning of fitting parameters from classic models of preferential solvation and the existence of postulated entities that are hard to be conceived in binary mixtures of ILs. © 2021 Elsevier B.V.
Keywords: Binary mixtures; Ionic liquids; Preferential solvation; Preferential-solvation index; Solvent-exchange model